Salivary alpha‐synuclein as a potential fluid biomarker in Parkinson's disease: A systematic review and meta‐analysis. Issue 1 (24th January 2022) - Kharel, Sanjeev; Ojha, Rajeev; Bist, Anil; Joshi, Surya Prakash; Rauniyar, Robin; Yadav, Jayant Kumar
Abstract: Introduction: Lewy bodies are the pathological hallmarks of Parkinson's disease. There is a need for effective biomarker that is cost effective, less invasive, and easily reproducible with good sensitivity and specificity and can be used to diagnose the condition early and track its severity and progression. Alpha‐synuclein (α‐syn), an integral component of the Lewy body, is found in saliva and can be a potential answer to the above concerns. Methods: PubMed, EMBASE, Google Scholar, and CNKI databases, along with additional sites, were searched from January 2010 to August 2021. Standard mean difference (Hedges' g) with 95% CI was used to show an association. Statistical analysis was done using STATA software version 16 (StataCorp). Results: We found a significant reduction in the mean difference of total salivary α‐syn among PD patients compared to healthy controls. However, the mean difference of oligomeric α‐syn and oligo/total salivary α‐syn ratio was significantly increased among PD patients compared to healthy controls. Conclusion: Our systematic review and meta‐analysis found that salivary α‐syn parameters (total, oligomeric, oligo/total) can be considered a simple, easy‐to‐use, cost‐effective, and reliable diagnostic biomarker for PD and its progression. Abstract : Alpha‐synuclein parameters (total, oligomeric, oligo/total) can be considered as a simple, easy to use, cost‐effective, and reliable diagnostic biomarker for PD and its progression.